2017
DOI: 10.1055/s-0037-1608839
|View full text |Cite|
|
Sign up to set email alerts
|

Difficult Cases in Robotic Arm-Assisted Total Knee Arthroplasty: A Case Series

Abstract: Sagittal deformity of the knee is commonly corrected to neutral biomechanical axis (±3 degrees) during total knee arthroplasty (TKA), which is a widely accepted goal. Recent advances in surgical technology have made it possible to accurately plan and fulfill these goals. One of these is robotic-assisted TKA, which has been noted to help increase accuracy and precision of restoring a neutral mechanical axis. While there are data confirming the ability of robotic devices to better correct knee alignment than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…RA-TKA is a surgical technique that has been found to have great patient satisfaction outcomes, optimal implant positioning, and soft tissue protection. [1][2][3][4] This study reported on the intraoperative surgical advantages of the RA-TKA system. The device was found to substantially help the surgeon achieve greater reduction in flexion and extension gaps, resulting in a more balanced knee intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RA-TKA is a surgical technique that has been found to have great patient satisfaction outcomes, optimal implant positioning, and soft tissue protection. [1][2][3][4] This study reported on the intraoperative surgical advantages of the RA-TKA system. The device was found to substantially help the surgeon achieve greater reduction in flexion and extension gaps, resulting in a more balanced knee intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic arm-assisted total knee arthroplasty (RA-TKA) is a surgical technique with several potential surgical and clinical advantages compared with manual technique TKA. [1][2][3][4] Recent reports have shown soft-tissue protection to be one of many potential clinical advantages of RA-TKA. 1 For example, RA-TKA creates a bony island on the tibial plateau, protecting the posterior cruciate ligament.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of these extra-articular deformities, standard operative techniques and instruments may not be reliable. Robotic-arm assisted technology was developed to help achieve a well-aligned and balanced knee in a variety of clinical scenarios [1][2][3][4] . Although prior case series have reported on the use of robotic-arm assisted devices for cases with severe angular deformity, there is a lack of data concerning the use of the robotic device for patients with other potentially complex surgical factors.…”
Section: Introductionmentioning
confidence: 99%